Respons Imun Mencit yang Diimunisasi dengan Cysticercus cellulosae (IMMUNE RESPONSE TO TAENIA SOLIUM CYSTICERCOSIS IN MICE) - Swacita, Ida Bagus Ngurah; Damriyasa, I Made; Dharmawan, Nyoman Sadra; Astawa, Nyoman Mantik; Apsari, Ida Ayu Pasti; Tenaya, I Wayan Masa (Jurnal Veteriner; Vol 16 No 2 (2015), 2015)
Cysticercosis is a zoonotic parasitic disease which is still problem in Indonesia. The purpose of thisstudy was to investigate immune responses of mice that had been immunized using Taenia solium larval(Cysticercus cellulosae) antigens originated from infected pigs. Three kinds of the C.cellulosaeantigens,secretory and whole antigens were used to immunize three different groups Balb/c mice consisted of 15animals. The serum samples before and after immunization were tested with ELISA test. The resultsshowed that the third antigens induced highly significant titre (P<0,01)compared to unimmunized animals.However no significant different (P>0,05) were found when the third antigens were compared. It wasconcluded that immunization with the three kinds of C. cellulosae antigens can cause immunity in mice.
Keywords: Cysticercus cellulosae, immune response, mice